1990
DOI: 10.1172/jci114732
|View full text |Cite
|
Sign up to set email alerts
|

Role of lipoprotein lipase in the regulation of high density lipoprotein apolipoprotein metabolism. Studies in normal and lipoprotein lipase-inhibited monkeys.

Abstract: Mechanisms that might be responsible for the low levels of high density lipoprotein (HDL) associated with hypertriglyceridemia were studied in an animal model. Specific monoclonal antibodies were infused into female cynomolgus monkeys to inhibit lipoprotein lipase (LPL), the rate-limiting enzyme for triglyceride catabolism. LPL inhibition produced marked and sustained hypertriglyceridemia, with plasma triglyceride levels of 633-1240 mg/dl. HDL protein and cholesterol and plasma apolipoprotein (apo) Al levels d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(54 citation statements)
references
References 62 publications
4
50
0
Order By: Relevance
“…Each 2-pool model had a circulating pool in equilibrium with a noncirculating pool. 33 In each case, it was confirmed that 2 pools fit the data significantly better than did a 1-pool model; a third pool was not required for any study.…”
Section: Calculations For the Experiments Performed With Micementioning
confidence: 85%
“…Each 2-pool model had a circulating pool in equilibrium with a noncirculating pool. 33 In each case, it was confirmed that 2 pools fit the data significantly better than did a 1-pool model; a third pool was not required for any study.…”
Section: Calculations For the Experiments Performed With Micementioning
confidence: 85%
“…The decrease in HDL cholesterol levels may be linked to the increase in serum triglycerides as hypertriglyceridemia is often associated with decreased HDL cholesterol levels (31)(32)(33). CETP facilitates the exchange of cholesterol ester in HDL for VLDL triglyceride, thus the abundant VLDL triglyceride in hypertriglyceridemia can promote this exchange and contribute to the decrease in HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally postulated that variation in plasma HDL-C levels are determined not by the rate at which they are produced, but rather by the rate of catabolism of their components. There are several known molecules that play a role in regulating plasma HDL-C levels (31), including HL (32)(33)(34)(35), LPL (36)(37)(38)(39)(40), lecithin:cholesterol acyl transferase (LCAT) (41,42), cholesterol ester transfer protein (CETP) (43), and phospholipid transfer protein (PLTP) (44). Intense study over the last few years has focused on the HDL particle in the context of reverse cholesterol transport and anti-oxidant properties, providing significant insights into the mechanism of HDL's antiatherogenic properties.…”
Section: Role In Lipoprotein Metabolismmentioning
confidence: 99%